展覧会評 朝鮮王朝の絵画と日本 - 江村 知子 (2010)
This exhibition review takes as its subject the exhibition entitled Paintings of Korea's Joseon Dynasty and Japan: The Art of a neighboring Kingdom that inspired Sôtatsu, Taiga and Jakuchû, held from November 2008 through July 2009 at the Tochigi Prefectural Art Museum, Shizuoka Prefectural Museum of Art, Sendai City Museum, and Okayama Prefectural Museum of Art. The novel aspect of this exhibition was not only the overview of Joseon dynasty painting, but also the detailed display of the influence of that painting on Japanese painting from the 15th to the 19th centuries. The exhibition featured works never before publicly displayed in Japan, and it was intentionally planned with the realization that the aims of the exhibition would raise certain issues. The exhibition was divided into two sections, with the first section Glory of Joseon dynasty painting, presenting an overview of Joseon dynasty paintings from the 14th through the 19th centuries. The first section also indicated the possibility that there are works that have been handed down as examples of Chinese or Japanese Muromachi period paintings that might actually be Korean paintings. The second section Aspects of Joseon dynasty painting from Japan, examined the influence of Korean painting on Japanese painting. While a large amount of earlier research has explored the influence of Chinese paintings on Japanese painting history, there has been almost no discussion of the influence of Korean paintings. This exhibition intentionally featured works that have shared subjects, expressive methods and techniques, and allowed visitors an opportunity to compare Korean paintings with Japanese paintings. The problems with this exhibition were related to its scale, with too many different periods and genres covered, but this article considers two particularly impressive points in terms of research on Edo period painting. The first point is the subject of the painting of puppies seen on the cover of the catalogue. In the exhibition, images of dogs by the painter of ...